2011
DOI: 10.1007/s00701-011-1200-5
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic acid (5-ALA)-induced fluorescence in intracerebral metastases: a retrospective study

Abstract: The majority of metastases (62%) were 5-AIF positive, suggesting a potential impact of 5-AIF for improved visualization of metastatic tumor tissue within the brain. However, residual 5-AIF after macroscopically complete resection of a metastasis needs to be interpreted with caution because of the limited specificity for detection of residual tumor tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
92
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 21 publications
5
92
1
1
Order By: Relevance
“…11,30 Interestingly, there was 1 biopsy among our study cohort that demonstrated ALA fluorescence in the presence of completely normal brain tissue. While additional samples are needed to support this finding, this may suggest that even in the absence of tumor, surrounding brain may take up ALA and fluoresce.…”
Section: Discussionmentioning
confidence: 86%
“…11,30 Interestingly, there was 1 biopsy among our study cohort that demonstrated ALA fluorescence in the presence of completely normal brain tissue. While additional samples are needed to support this finding, this may suggest that even in the absence of tumor, surrounding brain may take up ALA and fluoresce.…”
Section: Discussionmentioning
confidence: 86%
“…At the same time, no statistically significant effect on the overall survival rate was identified. Nevertheless, this technology has attracted an increased attention of neurosurgeons resulting in more reports on FN, as well as the application of this method for other central nervous system tumors [4,[7][8][9][10][11][12][13][14][15][16] including intracranial meningiomas [16][17][18][19][20]. However, the assessment of FN's sensitivity and specificity was not demonstrated clearly and in particular, no comparison was made between the data obtained from visible fluorescence, and the data obtained from laser biospectroscopy in meningiomas of different World Health Organization (WHO) grades.…”
Section: Introductionmentioning
confidence: 99%
“…5-ALA induced fluorescence is not seen in malignant gliomas only. Visualization and photodynamic therapy with 5-ALA of bladder, lung or gastrointestinal tumors has been established and for other cerebral intradural pathologies such as meningiomas, metastasis and medulloblastomas it has been recently explored [5,7,12,14,15,18,30].…”
mentioning
confidence: 99%